The Landau–Lifshitz equation in atomistic models - Ellis, M.O.A.; Evans, R.F.L.; Ostler, T.A.; Barker, J.; Atxitia, U.; Chubykalo-Fesenko, O.; Chantrell, R.W. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
The Landau–Lifshitz (LL) equation, originally proposed at the macrospin level, is increasingly used in Atomistic Spin Dynamic (ASD) models. These models are based on a spin Hamiltonian featuring atomic spins of fixed length, with the exchange introduced using the Heisenberg formalism. ASD models are proving a powerful approach to the fundamental understanding of ultrafast magnetization dynamics, including the prediction of the thermally induced magnetization switching phenomenon in which the magnetization is reversed using an ultra-fast laser pulse in the absence of an externally applied field. This paper outlines the ASD model approach and considers the role and limitations of the LL equation in this context.